Diversitas, Kemerataan, Dominansi dan Potensi Seed Bank Gulma Pada Tanah Perkebunan Rakyat Yang Berbeda Beda Di Lahan Kering - I Ketut Ngawit; Nihla Farida; Ni Made Laksmi Ernawati (LPPM Universitas Mataram, 2026)
The research aims to examine the diversity, dominance, equality, and frequency of weed species and to assess the potential of the soil as a weed seed bank in different types of plantations in arid regions. Descriptive research was conducted on plantations for coconuts, cashews, cocoa, coffee, and mixed gardens. Experiments to investigate the potential of the soil as a seed bank for weeds were carried out in the greenhouse of the Agricultural Faculty of Mataram University using a completely randomized one-factor design with five types of soil from the five plantations. The research results show that coconut plantation land and mixed gardens have the highest weed species diversity index and evenness with low dominance. In contrast, cashew, cocoa, and coffee plantation lands show high species dominance with low diversity and evenness, resulting in five highly dominant weed species, namely: P. Conjugatum, A. Compressus, D. Esculentum, B. Spicata, and S. torvum. Coconut plantations and mixed gardens show a significantly higher number of species, populations, and the dry biomass weight of weed grasses and reeds compared to almonds, cocoa, and coffee, as well as a faster growth time of the weed seed bank, reflecting the ecological conditions that support the soil's potential as a weed seed bank.